Shoulder biomechanics of para-table tennis: a case study of a standing class para-athlete with severe leg impairment - Kong, P. W.; Yam, J. W. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Both able-bodied and Class 7 para-table tennis players compete while standing, but do they use the same techniques to hit the ball? This case study examined the shoulder joint kinematics of a highly skilled para-table tennis player with severe leg impairment.